2010
DOI: 10.1002/lary.21063
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for competency in flexible laryngoscopy

Abstract: Our results suggest that it takes six attempts on average for a novice to become competent in performing flexible laryngoscopy. This finding has implications for residency programs because it indicates the learning curve can be overcome in the laboratory rather than with patients. Laryngoscope, 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…This suggests that the benefits of repetition quickly become appreciable. A recent study has shown that learners become competent after 6 endoscopies [6]. Our study is in keeping with this notion of rapid skill acquisition with repeat endoscopy.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the benefits of repetition quickly become appreciable. A recent study has shown that learners become competent after 6 endoscopies [6]. Our study is in keeping with this notion of rapid skill acquisition with repeat endoscopy.…”
Section: Discussionsupporting
confidence: 90%
“…The optimal method for examining the larynx is using a flexible fiberoptic scope videolaryngoscopy, which provides documentation for review and comparison of function before versus after surgery, if needed. Recent work has suggested that an average of 6 attempts for novices are necessary in order to become technically competent in performing flexible laryngoscopy . Interpretation of all laryngeal findings may take greater clinical experience.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, the scope operator and the offsite reviewer did not always agree on the ability to visualize anatomical subsites, which is a more specific characteristic than diagnosis alone. This may be due to the difference in training levels because it has been found that laryngoscopy skills improve with increased experience . This further demonstrates the value of a recorded exam—instead of a verbal exchange of information alone—for communication between residents and attendings.…”
Section: Discussionmentioning
confidence: 91%